Urban security in southern Europe. (May 2013) - Recasens, Amadeu; Cardoso, Carla; Castro, Josefina; Nobili, Gian Guido
This article examines comparative developments in the politics, policies and practices in public safety and crime prevention across Italy, Portugal and Spain. The article begins by plotting the relatively recent history of what may be termed 'the preventive turn' in this region of Europe. It is argued that systematic thinking and coordinated policy and practice regarding crime prevention and public safety remain limited and fragile, with notable exceptions in some cities (such as Barcelona) and regions (such as Emilia-Romagna) across the three countries. Overall, the progress of local safety and security programmes in southern Europe is uneven and fragmented when compared with much of northern Europe. In turn, the current pressures on these countries' governmental capacities and resources in the light of the profound economic crisis they are undergoing are discussed and their implications for progressive as against repressive urban security management assessed. The article then compares the major areas of convergence and divergence across the three countries.